The influence of the real estate investment trust in the real estate sector on the Costa del Sol - Ricardo Urrestarazu Capellán; José Luis Sánchez Ollero; Alejandro García Pozo (European Research on Management and Business Economics, 2021)
The presence of the real estate investment trust in the Spanish real estate market since 2013 has led a significant number of the housing stock being offered for rent in the most popular cities around the country. In the specific case of the Costa del Sol, it is necessary to evaluate the participation of these companies in the establishment of a stable business fabric of housing for rent as well as in the development sector for home sales. In addition, its membership of international financial circuits means that the effect of financing the economy on urban environments has to be taken into account.In order to assess the weight of the real estate investment trust in the development of the Costa del Sol, we turned to data on housing developments for sale provided by the main Internet real estate portals are used, comparing their market share with that of other national and local players The main conclusion is that this type of company has not opted for professional marketing of housing offered for residential rental in the province, but nevertheless, they have become the leading companies in the real estate development sector in the province by number of homes offered.To achieve this objective, this document has first opted for a study of literature review that includes the contributions of Spanish and international social scientists on the processes of transmission of financial capital to the real estate sector, the characteristics of financial actors and their patterns of behavior, the factors that enable and facilitate their activity; as well as the transformations that have undergone today and that have allowed them to expand their investments, concluding with the economic and social consequences of all this.Likewise, this analysis has also been deepened with the main characteristics of RETTs have, also attending the main magnitudes and figures related to it, provided by Spanish public institutions.Finally, current data have been obtained on the new construction market of real estate of the Costa del Sol, using reports and statistics prepared by business study centers, and professional organizations in the sector. This information has allowed to know the number of homes built and put up for sale in recent years, as well as their geographical distribution or the nature of the real estate developer, which has allowed to show the main characteristics of this market.These contributions and the data on the number, location and origin of the real estate developer of new construction homes, confirm the influence that the international financial agents have on the real estate sector of the province of Malaga, with an important participation in the tourist sector, focusing its activity on the real estate development of housing sales, while it has a marginal role in the supply of residential rental housing.Taking advantage of the dynamics of the growth of the tourism sector, REITs have been the pioneers of the growth of the real estate sector in Malaga in the last four years, becoming the companies with the greatest market power and the greatest number of homes built in the sector, above those built by national and local housing developers. However, the goal set by the public sector for REITs to offer a professional rental housing stock has not been achieved.